High-efficiency activation of the C–H bond to synthesize p-methoxy benzaldehyde over a MnO2/CNT/Gr catalyst - Wu, Yi; Tang, Mengyi; Zhong, Yan; Guo, Zhenlong; Li, Kexin; Yang, Youdi; Li, Qiang (New journal of chemistry, 2022)
p-Methoxy benzaldehyde (p-MBA) has been widely used in the fields of spices, medicine, cosmetics and food additives due to its remarkable properties, and can be synthesized by oxidizing the C–H bond of p-methoxy toluene (p-MT) to an aldehyde group. However, the conversion is subject to harsh reaction conditions and low selectivity. Electrosynthesis obviates the use of additional costly and toxic oxidants, and provides an efficient and environmentally friendly route to achieve this conversion. In this study, the electrocatalytic oxidation of p-MT for the synthesis of p-MBA over a graphite electrode loaded with MnO2/carbon nanotube (CNT)/graphene (Gr) catalyst was investigated. The excellent structure significantly improved the stability and dispersibility of active sites, increased electron transmission speed, and adjusted the adsorption and desorption efficiency of the reactants. High selectivity of p-methoxy benzaldehyde was achieved by this green C–H bond functionalization: 81.03% faradaic efficiency and 82.73% selectivity of p-MBA were obtained.